Characterization and Application of Na/SnO? Catalyst in Biodiesel Production: Insights into Structure and Performance - Zeng Feihu Zeng; Chen Xiaohua; Feng Wang; SyYi Sim; Lu Huangteng (International Journal of Integrated Engineering, 2026)
Biodiesel production via transesterification of rapeseed oils offers a sustainable substitute for fossil fuels, with solid base catalysts playing a key role in enhancing reaction efficiency. This study reports the synthesis a Na/SnO? solid base catalyst and its performance evaluation using the transesterification reaction of rapeseed oil. SnO? was synthesized via a precipitation method and subsequently combined with sodium metal under a nitrogen atmosphere. Sodium species interacted with SnO? through the formation of NaOH and Na?O, bonding to surface hydroxyl groups or incorporating into lattice defects to generate strong basic sites (Hammett range: 11.2–15.6). Structural and surface properties were characterized by XRD, FT-IR, TG-DSC, SEM, and Hammett titration. Optimal catalytic performance was achieved under conditions of pH 8, calcination at 600°C for 3 hours, 0.015 mol surfactant concentration, and 3.75 wt.% sodium loading, yielding a biodiesel conversion rate of 93.6%. Results demonstrated that moderate calcination was critical to ensuring high crystalline and active site availability, while excessive thermal treatment induced sintering and deactivation. This work presents an innovative method to stabilize Na-based active sites and prevent SnO? dissolution, offering a viable route for designing high-performance solid superbases for green biodiesel synthesis.